Can computational fluid dynamics simulations predict a distal stent graft-induced new entry after frozen elephant trunk operation? - Osswald, Anja; Tsagakis, Konstantinos; Thielmann, Matthias; Shehada, Sharaf-Eldin; Jánosi, Rolf Alexander; Akhyari, Payam; Karmonik, Christof (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesDistal stent graft-induced new entry (dSINE) is a complication after frozen elephant trunk (FET) procedure. The purpose of this study was to identify the hemodynamic profile of the aorta associated with dSINE development using computational fluid dynamics (CFD) simulation.Methods30 patients, 15 who had developed a dSINE (dSINE group) and 15 without any further vascular events (control group), undergoing an FET operation for aortic dissection were retrospectively included in this CFD study. Patient-specific 3D surface models of the aortic lumen were reconstructed from computed tomography angiographic (CTA) datasets, utilizing the CTA acquired before dSINE onset. Steady-state CFD simulations were performed with laminar blood flow and zero-pressure outlet conditions to assess velocity magnitudes, wall shear stress (WSS), and vorticity within the stent graft (SG), its distal landing zone and further downstream.ResultsIn the dSINE group, WSS was significantly elevated distal to the SG compared to WSS within the SG and at its landing (2.95 ± 1.47 Pa vs. 1.56 ± 0.71 Pa and 2.00 ± 0.81 Pa, p < 0.001 for both comparisons). In the control group, this distinct pattern of distal WSS elevated distal to the SG in comparison to other locations was not observed. Similarly, vorticity increased significantly distally to the SG in the dSINE group, but not in the control group.ConclusionsIncreased WSS distal to the SG compared to within the SG and its landing zone seem to be associated with dSINE development. CFD can be a useful tool to understand SG-induced hemodynamic changes in the aorta to help predict complications after FET.